Experiences of health care transition voiced by young adults with type 1 diabetes: a qualitative study - Garvey KC; Beste MG; Luff D; Atakov-Castillo A; Wolpert HA; Ritholz MD (Adolescent Health, Medicine and Therapeutics, 2014)
Katharine C Garvey,1,5 Margaret G Beste,2 Donna Luff,3,5 Astrid Atakov-Castillo,2 Howard A Wolpert,2,5 Marilyn D Ritholz4–61Division of Endocrinology, Boston Children’s Hospital, Boston, MA, USA; 2Adult Section, Joslin Diabetes Center, Boston, MA, USA; 3Institute for Professionalism and Ethical Practice, Boston Children's Hospital, Boston, MA, USA; 4Behavioral and Mental Health Unit, Joslin Diabetes Center, Boston, MA, USA; 5Harvard Medical School, Boston, MA, USA; 6Department of Psychiatry, Boston Children's Hospital, Boston, MA, USAObjective: This qualitative study aimed to explore the experience of transition from pediatric to adult diabetes care reported by posttransition emerging adults with type 1 diabetes (T1D), with a focus on preparation for the actual transfer in care.Methods: Twenty-six T1D emerging adults (mean age 26.2±2.5 years) receiving adult diabetes care at a single center participated in five focus groups stratified by two levels of current glycemic control. A multidisciplinary team coded transcripts and conducted thematic analysis.Results: Four key themes on the process of transfer to adult care emerged from a thematic analysis: 1) nonpurposeful transition (patients reported a lack of transition preparation by pediatric providers for the transfer to adult diabetes care); 2) vulnerability in the college years (patients conveyed periods of loss to follow-up during college and described health risks and diabetes management challenges specific to the college years that were inadequately addressed by pediatric or adult providers); 3) unexpected differences between pediatric and adult health care systems (patients were surprised by the different feel of adult diabetes care, especially with regards to an increased focus on diabetes complications); and 4) patients’ wish list for improving the transition process (patients recommended enhanced pediatric transition counseling, implementation of adult clinic orientation programs, and peer support for transitioning patients).Conclusion: Our findings identify modifiable deficiencies in the T1D transition process and underscore the importance of a planned transition with enhanced preparation by pediatric clinics as well as developmentally tailored patient orientation in the adult clinic setting.Keywords: young adults, chronic illness, type 1 diabetes mellitus, transition to adult care